Investigation of the Relationship Between Eating Behavior and Student Learning Achievement - Milleana Arsyanti; Anindhita Shahbi Syagata (The Indonesian Institute of Science and Technology Research, 2022)
The desire to eat is one of the dimensions of the eating environment. It is mainly seen in attitude, skill, and knowledge. This study aims to investigate the relationship between attitudes, skills, and eating knowledge with student learning achievement. This research is analytical observational research with a cross-sectional design. The subjects were university students in Lampung. The sampling of 196 students was collected using a non-probability with snowball sampling techniques. The data include respondents' characteristics, learning achievements, and eating desires (attitudes, skills, and knowledge). The data analysis was carried out using the Chi-square test to determine the relationship between eating attitudes, eating skills, and eating knowledge, with the student learning achievement. The results showed that most of the subjects (91.33%) had a good eating attitude, (69.90%) had less eating skills, and (51.53%) also had less eating knowledge. In this study, it is revealed that there is no significant relationship between eating attitudes, eating skills, and eating knowledge with the student learning achievement.